SPACIAL INDEXES AND BIOLOGICAL DIVERSITY OF ITANHAÉM, SÃO PAULO, BRAZIL - Ribeiro Botelho de Carvalho Maria, Tamara; Biondi, Daniela; Zamproni, Kendra (Floresta, 2019)
Many managers have studied the afforestation as a mitigating tool for the problems caused by urbanization, since the specific knowledge of each municipality is fundamental for proper planning in relation to the species used, the number of trees and the location in the municipality. The present research had the objective of evaluating the spatial and biological diversity indexes of the road arborization of the city of Itanhaém - SP. For the accomplishment of the research, a qualitative and quantitative inventory of the arborization was done to obtain the coverage indices and tree density, index of full occupation, current occupation and the deficit of afforestation and the performance index of the species. There is 1 tree for each 100 m² of sidewalk in the municipality, 2.35% of the sidewalks are covered by the crown of the trees and the municipality presents only 21.1% of the ideal afforestation. The municipality had a high diversity index of Shannon H ’= 3.45 and Simpson dominance λ = 0.082. The native species with the best performance index was Schinus terebinthifolius. Although there are species diversity in the municipality, the current situation demonstrates the scarcity of trees, indicating the need for intensification in the planting of trees in the road system.